Stack of cellular lamellae forms a silvered cortex to conceal the opaque organ in a transparent gastropod in epipelagic habitat - Daisuke Sakai; Jun Nishikawa; Hiroshi Kakiuchida; Euichi Hirose (PeerJ, 2022)
Background Gelatinous zooplankton in epipelagic environments often have highly transparent bodies to avoid detection by their visual predators and prey; however, the digestive systems are often exceptionally opaque even in these organisms. In a holoplanktonic gastropod, Pterotrachea coronata, the visceral nucleus is an opaque organ located at the posterior end of its alimentary system, but this organ has a mirrored surface to conceal its internal opaque tissue. Results Our ultrastructural observation proved that the cortex of the visceral nucleus comprised a stack of thin cellular lamellae forming a Bragg reflector, and the thickness of lamellae (0.16 µm in average) and the spaces between the lamellae (0.1 µm in average) tended to become thinner toward inner lamellae. Based on the measured values, we built virtual models of the multilamellar layer comprising 50 lamellae and spaces, and the light reflection on the models was calculated using rigorous coupled wave analysis to evaluate their properties as reflectors. Our simulation supported the idea that the layer is a reflective tissue, and the thickness of the lamella/space must be chirped to reflect sunlight as white/silver light, mostly independent of the angle of incidence. Conclusions In P. coronata, the cortex of the visceral nucleus comprised multicellular lamellae that form a chirped Bragg reflector. It is distinct in structure from the intracellular Bragg structures of common iridophores. This novel Bragg reflector demonstrates the diversity and convergent evolution of reflective tissue using reflectin-like proteins in Mollusca.